Antecedents and Outcomes of Modular Production in the Brazilian Automobile Industry: A Grounded Theory Approach - Kotabe, Masaaki; Ronaldo Parente; Murray, Janet Y. (Journal of international business studies, 2007)
Our paper focuses on how foreign automobile manufacturers in Brazil have implemented and benefited from strategic modularization. Based on our case studies and in-depth interviews, we developed a theoretical framework to examine the antecedents and outcomes of strategic modularization. Our theoretical framework suggests that strategic modularization may help improve a firm's positional advantage by reducing the cost of managing tacit knowledge. In addition, the adoption of strategic modularization influences the nature of relationships with major suppliers, further blurring the boundaries of the firm.